2018
DOI: 10.1098/rspb.2018.0335
|View full text |Cite
|
Sign up to set email alerts
|

Morph-specific artificial selection reveals a constraint on the evolution of polyphenisms

Abstract: Theory predicts that the evolution of polyphenic variation is facilitated where morphs are genetically uncoupled and free to evolve towards their phenotypic optima. However, the assumption that developmentally plastic morphs can evolve independently has not been tested directly. Using morph-specific artificial selection, we investigated correlated evolution between the sexes and male morphs of the bulb mite Large 'fighter' males have a thick and sharply terminating pair of legs used to kill rival males, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 47 publications
(67 reference statements)
2
23
0
Order By: Relevance
“…Selecting on the relative leg width of only the fighter male ART, they observed a response in relative leg width in not only the fighters, but also a correlated response in the scrambler ART and females. While one conclusion that could be made from these results is that a complete uncoupling between the ARTs is not necessary for tactical dimorphism to evolve (Buzatto et al 2018), these results also demonstrate that the existence of tactical dimorphism does not necessarily indicate that IATC has been resolved ( Fig. 2c).…”
Section: When To Expect and How To Detect Iatcmentioning
confidence: 78%
See 3 more Smart Citations
“…Selecting on the relative leg width of only the fighter male ART, they observed a response in relative leg width in not only the fighters, but also a correlated response in the scrambler ART and females. While one conclusion that could be made from these results is that a complete uncoupling between the ARTs is not necessary for tactical dimorphism to evolve (Buzatto et al 2018), these results also demonstrate that the existence of tactical dimorphism does not necessarily indicate that IATC has been resolved ( Fig. 2c).…”
Section: When To Expect and How To Detect Iatcmentioning
confidence: 78%
“…When the correlations between traits were compared to correlations across the genetically influenced sexes, which exhibited sexual dimorphism, in both species the correlations across the ARTs were lower. The existence of genetic correlations for traits between ARTs in bulb mites was more recently confirmed using artificial selection (Buzatto et al 2018). Selecting on the relative leg width of only the fighter male ART, they observed a response in relative leg width in not only the fighters, but also a correlated response in the scrambler ART and females.…”
Section: When To Expect and How To Detect Iatcmentioning
confidence: 84%
See 2 more Smart Citations
“…Buzatto et al (2018) found that bidirectional selection for leg width in R. echinopus fighters resulted in positively correlated responses in leg sizes of scramblers and females. This suggests that the development of leg size is not fully decoupled between fighters and scramblers (also see Pike et al 2017) or females.…”
Section: Discussionmentioning
confidence: 99%